Development of Self Competence and Supervision to Achieve Professionalism - Sinambela, Ella Anastasya; Mardikaningsih, Rahayu; Arifin, Samsul; Ayu, Halvinda Dyah (Journal of Islamic Economics Perspectives, 2020)
Abstract Professionalism is the main requirement of every company because the skills possessed by employees will make a meaningful contribution to the realization of company goals. Employees who have an attitude of professionalism have the ability to understand duties and responsibilities, maintain relationships and social interaction in the workplace and focus on work matters. Work professionalism is one of the most important aspects of achieving success at work. This study aims (a) to analyze and determine the effect of competence on employee professionalism; (b) to analyze and determine the effect of work supervision on employee professionalism; and (c) to analyze and determine the effect of competency and work supervision simultaneously on employee professionalism. This research was conducted by involving 91 respondents and using multiple linear regression analysis with the help of the SPSS Ver program. 25. The population involved in this research is the production employees of PT Unicharm Indonesia. The results showed that work competency and supervision had a significant positive effect partially and simultaneously on employee professionalism. Keywords: competence, supervision, professionalism